Membrane position of ibuprofen agrees with suggested access path entrance to cytochrome P450 2C9 active site - Berka, Karel; Hendrychová, Tereza; Anzenbacher, Pavel; Otyepka, Michal (The journal of physical chemistry. A, 2011)
Cytochrome P450 2C9 (CYP2C9) is a membrane-anchored human microsomal protein involved in the drug metabolism in liver. CYP2C9 consists of an N-terminal transmembrane anchor and a catalytic cytoplasmic domain. While the structure of the catalytic domain is well-known from X-ray experiments, the complete structure and its incorporation into the membrane remains unsolved. We constructed an atomistic model of complete CYP2C9 in a dioleoylphosphatidylcholine membrane and evolved it by molecular dynamics simulations in explicit water on a 100+ ns time-scale. The model agrees well with known experimental data about membrane positioning of cytochromes P450. The entry to the substrate access channel is proposed to be facing the membrane interior while the exit of the product egress channel is situated above the interface pointing toward the water phase. The positions of openings of the substrate access and product egress channels correspond to free energy minima of CYP2C9 substrate ibuprofen and its metabolite in the membrane, respectively.
Keywords: Molecular Dynamics Simulation; simulace molekulární dynamiky; Aryl Hydrocarbon Hydroxylases; Models, Molecular; Membranes, Artificial; povrchové vlastnosti; fosfatidylcholiny; Humans; Cytochrome P-450 CYP2C9; membrány umělé; vazebná místa; krystalografie rentgenová; ibuprofen; Phosphatidylcholines; cytochrom P450 CYP2C9; Ibuprofen; Surface Properties; Binding Sites; aromatické hydroxylasy; lidé; molekulární modely; Crystallography, X-Ray